Emergent Brazil : Key Perspectives on a New Global Power - Needell, Jeffrey D. (Book collections on Project MUSE., 2015)
This collection of sixteen essays examines the impact of Brazilian trends, institutions, culture, and religion on the world through accelerating processes of globalization.